Real property : ownership and registration - Mamalateo, Victorino C.; Mamalateo-Jusay, Mary Joy B. (Manila : Rex Book Store, 2021)
"With the same shared vision as the first edition of this book written in 2011, this revised edition which is long overdue is intended to provide the vast number of individual or corporate property owners or potential property owners or buyers, whether engaged or not engaged in real estate business, and the steadily increasing number of real estate service practitioners, such as consultants, appraisers, brokers and salespersons, as well as other professionals, such as lawyers and certified public accountants, greater ease by having a comprehensive but concise reference book containing the significant laws, rules and regulations, and jurisprudence relevant to the subject matter available. This book was also written in a straightforward and comprehensible format having in mind the growing number of students pursuing a degree in real estate management which was made a mandatory requirement under the RESA Law to qualify to take the licensure examinations for real estate service practitioners."
Includes appendix.
English.
Keywords: Real estate investment; Real estate business